Aktivitas Antidiabetes Kombinasi Ekstrak Daun Jambu Biji dan Daun Rambutan pada Tikus Putih Jantan Galur Wistar (Rattus norvegicus) yang Diinduksi Streptozotocin - Pradani, Lintang Oktavian; Widiastuti, Tri Cahyani; Khuluq, Muhammad Husnulq (Jurnal Ilmiah Medicamento, 2025)
Diabetes mellitus is a metabolic disorder characterized by elevated blood glucose levels due to insulin deficiency or resistance. Long-term use of oral antidiabetic drugs can lead to adverse effects and high costs, making safer alternatives necessary. Herbal medicines derived from natural sources offer a promising option with relatively fewer side effects. Guava (Psidium guajava) and rambutan (Nephelium lappaceum) leaves are known to contain bioactive compounds with potential antihyperglycemic properties. This study aimed to determine the optimal dose combination of guava and rambutan leaf extracts for controlling blood glucose levels in streptozotocin-induced Wistar rats (Rattus norvegicus). The extracts were prepared using maceration, standardized, and analyzed by Thin Layer Chromatography (TLC) to identify active compounds. Thirty-two rats were divided into eight groups: healthy control, negative control (CMC-Na 0.5%), positive control (glimepiride 0.036 mg/kg BW), single extract of guava leaves (50 mg/kg BW), single extract of rambutan leaves (70 mg/kg BW), and three combinations of extracts (50%:50%, 75%:25%, and 25%:75%). Diabetes was induced intraperitoneally using streptozotocin. Blood glucose levels were measured every seven days for 21 days using a glucometer. Data were analyzed using One-Way ANOVA followed by Games-Howell post hoc test. The extracts met standardization requirements and contained flavonoids. The highest glucose reduction (72%) was observed in the 25%:75% combination (guava:rambutan), showing a significant difference compared to the negative control. These findings suggest that the combination of guava and rambutan leaf extracts has strong potential as a natural antidiabetic agent.